2011
DOI: 10.1016/j.brainresbull.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking maternal smoking and pharmacotherapy of preterm labor: Fetal nicotine exposure enhances the effect of late gestational dexamethasone treatment on noradrenergic circuits

Abstract: Smoking during pregnancy increases the risk of preterm delivery, which in turn necessitates the common use of glucocorticoids to prevent respiratory distress syndrome. Accordingly, there is a substantial population exposed conjointly to fetal nicotine and glucocorticoids (typically dexamethasone). We administered nicotine to pregnant rats throughout gestation, using a regimen (3 mg/kg/day by osmotic minipump) that maintains plasma nicotine levels within the range seen in smokers; on gestational days 17, 18 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
(79 reference statements)
3
11
0
3
Order By: Relevance
“…As has been shown in prior studies of the developmental neurotoxicity of nicotine and chlorpyrifos individually (Aldridge et al, 2004; Levin et al, 2001, 2002; Rauh et al, 2012; Slotkin, 2005; Slotkin et al, 2001, 2013, 2014a; Slotkin and Seidler, 2011), we found a high degree of sex-selectivity of the effects of each agent and of the combination treatment. As presented in those earlier reports, this does not likely represent a difference in the initial effects of the toxicants but rather the sex-dependence of adaptive mechanisms, such as neural cell replacement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As has been shown in prior studies of the developmental neurotoxicity of nicotine and chlorpyrifos individually (Aldridge et al, 2004; Levin et al, 2001, 2002; Rauh et al, 2012; Slotkin, 2005; Slotkin et al, 2001, 2013, 2014a; Slotkin and Seidler, 2011), we found a high degree of sex-selectivity of the effects of each agent and of the combination treatment. As presented in those earlier reports, this does not likely represent a difference in the initial effects of the toxicants but rather the sex-dependence of adaptive mechanisms, such as neural cell replacement.…”
Section: Discussionsupporting
confidence: 86%
“…We minimized stress contributions by including control pump implants, followed by either postnatal vehicle or chlorpyrifos administration, thus permitting comparison of the doubly-exposed group to those receiving only the prenatal stressor. Furthermore, the surgery was carried out on the fourth day of gestation, two days prior to the implantation of the embryo in the uterine wall, so that there was no communication between maternal and fetal circulation at the time of surgery; indeed, any anomalies at that stage typically lead to failure of the embryo to implant or to spontaneous abortion, neither of which were noted here or in earlier studies with the same design (Slotkin et al, 2010; Slotkin and Seidler, 2010, 2011). Nevertheless, we cannot absolutely rule out a stress × drug interaction.…”
Section: Discussionmentioning
confidence: 93%
“…Существуют данные, что различные реакции на пренатальное воздействие никотина связаны с по-лом [109,160,173]. Особая чувствительность жен-ского пола к никотину может быть обусловлена центральными эффектами половых стероидных гор-монов, прежде всего опосредованной ими половой дифференцировкой мозга и глубоким организую-щим эффектом половых гормонов на нейрональные структуры, функции и нейрохимию мозга [30,151].…”
Section: воздействие никотина связано с поломunclassified
“…Однако известно, что НА-ергические нейроны в раз-вивающемся мозге особо чувствительны к прена-тальному воздействию никотина [173,193] в связи с ранней активацией этой нейромедиаторной си-стемы [105] в мозге развивающегося организма. Хотя однократное воздействие никотина на самку значительно увеличивает НА-ергическую актив-ность [173], более значимые эффекты наблюдаются после хронического воздействия [143,173]. Поэто-му было выдвинуто предложение, что стимулирую-щие эффекты никотина связаны с гипоксией [170].…”
Section: действие никотина на на-ергическую систему мозгаunclassified
See 1 more Smart Citation